Knowledge and innovation for development the Sisyphus challenge of the 21st century - Sagasti, Francisco R.; Edward Elgar Publishing (Cheltenham, U.K. ; Northhampton, Mass. : E. Elgar, 2004)
This text provides a comprehensive introduction to the many different issues related to the Sisyphean task of building science and technology capabilities in developing countries. It attempts to answer crucial questions including: how can knowledge be utilized to improve the human condition, and how can we bridge the growing knowledge divide between those who produce and use modern science and technology--and those who do not?
1. Knowledge, technology and production : a conceptual framework -- 2. A brief historical perspective -- 3. The knowledge explosion and its manifestations -- 4. The knowledge divide and disparities in developing country capacities -- 5. Strategies and policies for building an endogenous science and technology base.
Includes bibliographical references (p. 133-147) and index.
Keywords: Science and state -- Developing countries; Technology and state -- Developing countries; Research -- Developing countries; Electronic books